Case Series: Genetic mimics of hypertrophic cardiomyopathy in elderly - Chumakova, Olga S.; Drobyazko, Olga A.; Stepanova, Elena A.; Pushkov, Alexander A.; Savostyanov, Kirill V.; Zateyshchikov, Dmitry A. (Frontiers in Cardiovascular Medicine, 2025)
Hypertrophic cardiomyopathy (HCM) is the most prevalent genetic cardiac disorder, primarily driven by pathogenic nucleotide variants (PNVs) in the genes that encode sarcomeric proteins. Such PNVs cause a disruption of cardiomyocytes. Notably, up to 5% of patients with an HCM phenotype may actually have other conditions that mimic HCM. These rarer, predominately hereditary syndromic diseases can be clinically suspected through specific “red flags”. However, in elderly patients, extracardiac manifestations may be subtle or misattributed to other diseases or the aging process, complicating the clinical diagnosis. In such cases, genetic testing becomes essential for achieving an accurate diagnosis and guiding specific treatment strategies. Screening younger relatives for genetic predispositions offers additional benefits in the era of emerging novel therapeutic technologies. In this study, we present comprehensive genetic and clinical characterization of three cases of HCM mimics, including amyloidosis, Fabry disease (FD), and desminopathy caused by TTR p.V50M, GLA p.N215S, and DES p.R355* PNVs, respectively. We also provide a brief review of the literature addressing the diagnostic challenges of associated with these rare conditions.